An Open Operating System for a Single-User Machine - Lampson, Butler; Sproull, Robert F. (7th ACM Symposium on Operating Systems Principles, 1979)
The file system and modularization of a single-user operating system are described. The main points of interest are the openness of the system, which establishes no sharp boundary between itself and the user’s programs, and the techniques used to make the system robust.
Published in ACM Operating Systems Review 11, 5 (Dec. 1979), pp 98-105. For the original, see the related file.